Technological and industrial applications associated with intelligent logistics - Ochoa-Zezzatti, Alberto; Oliva, Diego; Perez, Angel Juan (Lecture Notes in Intelligent Transportation and Infrastructure (LNITI), 2021)
This book helps the reader to identify how different organizations in the context of diverse societies deploy their resources and leverage their capabilities to achieve better performance of its various labor skills, marketing, social responsibility and management capacity. Intelligent Logistics is a complex phenomenon that has become critical for companies to reach their development locally and internationally. On the one hand, macro-factors and market structure influence in business competitiveness, but also in a regional or sector context. The internal aspects and the use of various business tools contribute to the ability to create value in an organization. It is of utmost importance to understand the relevance of crucial aspects in the technological future that should be known and implemented by the Z generation of its incidence in the use of organizational models linked to artificial intelligence. Every innovative aspect in the use of new technologies for the distribution of goods and services will be crucial in a globalized world. An avant-garde society will require improved decision-making regarding Logistics 4.0 and its implementation in our lives respecting the environment and being sustainable together with invaluable principles of generating tacit knowledge for future generations.